Formulasi dan Uji Stabilitas Mekanik Hand and Body Lotion Sari Buah Tomat (Licopersicon esculentum Mill.) sebagai Antioksidan - Anasthasia Pujiastuti; Monica Kristiani (Jurnal Farmasi Indonesia, 2019)
Antioxidants are contained in various types of fruits and vegetables. One of them is tomato (Lycopersicumesculentum Mill). Tomato has lycopene, flavonoids and vitamin C as antioxidants. Tomato can be made into fruit juice using the pressing method. Tomato extracts can be made in pharmaceuticals in the form of hand and body lotion (H&B lotion). The aim of this study is to recognize the physical characteristics and stability of mechanical H&B fruit extracts and to know the antioxidant activity.The free variable in this study is the concentration of fruit juice as active as 20%, 35%, and 50%. The binding variable from this study is the physical characteristics of the tomato juice extract, which is bioleptic, pH, viscosity, emulsion type, mechanical stability lotion and activity of antioxidant. The data obtained from the research results are compared with those in the literature whose relevance to statistical analysis between 95% trusts.The results of the research for physical characteristic show that concentrated fruit extract were not affected by the physical equipment of H&B lotion. The results for stability of mechanical H&Blotion fruit extracts test show that all the formulations had the phase separation. The test also shows that H&Blotion of Tomato had an activity of oxidation with IC50 value in formula I 5.697 μg/mL, formula II 6,530 μg/mL, and formula III 5,106 μg/mL.